Death due to lightning strike- An opinion of circumspection - Chawla, Hitesh; Yadav, Kapil; Shankar, Shiv; Vashista, Bhushan; Tyagi, Ashish; Kumar, Rajeev (Journal of Indian Academy of Forensic Medicine, 2020)
Death due to lightning is an unusual occurrence in routine autopsy practice. Majority of lightning deaths are not witnessed or happen  in situations that are either perplexing or surroundings are such that it may be challenging to reconstruct the actual events as they  happened. Medico-legally, suspicions may be nurtured of foul play because of the existence of burns, wounds, fractures, lacerations  and torn clothes in such cases. Autopsy findings are not ample for determination of manner of death in cases of lightning. Death due  to lightning strike is an opinion of guardedness, especially when there is a single causality assumedas a consequence of lightning.  Examination of the clothes and exploration of the scene of crime gives significant clues to the forensic pathologist. Witness  testimonies and meteorology reports form a vital tool in the exploration of the manner of death for bodies found in outdoor,  particularly in fields.
Keywords: Lightning; Burns; Keraunomedicine